2008
DOI: 10.1038/leu.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL mutants spread resistance to non-mutated cells through a paracrine mechanism

Abstract: Patients with chronic myeloid leukemia who become resistant to the Abl kinase inhibitor imatinib can be treated with dasatinib. This sequential treatment can lead to BCR-ABL mutations conferring broad resistance to kinase inhibitors. To model the evolution of resistance, we exposed the mouse DA1-3b BCR-ABL þ leukemic cell line to imatinib for several months, and obtained resistant cells carrying the E255K mutation. We then exposed these cells to dasatinib, and obtained dasatinib-resistant cells with composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…5 A remote alternative explanation for an independent role of minor P2RY8-CRLF2-positive clones would be that they alone could perhaps render their fusion-negative leukemic counterparts resistant through a paracrine route in a similar manner as has been demonstrated for minor mutant BCR-ABL-positive clones in comparable situations. 30 However, the absence of P2RY8-CRLF2-positive clones in most relapses hardly supports such a possibility.…”
Section: Discussionmentioning
confidence: 91%
“…5 A remote alternative explanation for an independent role of minor P2RY8-CRLF2-positive clones would be that they alone could perhaps render their fusion-negative leukemic counterparts resistant through a paracrine route in a similar manner as has been demonstrated for minor mutant BCR-ABL-positive clones in comparable situations. 30 However, the absence of P2RY8-CRLF2-positive clones in most relapses hardly supports such a possibility.…”
Section: Discussionmentioning
confidence: 91%
“…20 Paracrine protection of imatinib-sensitive leukemic cells by low levels of imatinib-resistant cells with BCR-ABL1 mutations has also been reported. 21 A recent study found no correlation between the number of low-level mutations (detection limit 1%) in tyrosine kinase inhibitornaïve, Philadelphia chromosome-positive acute lymphoblastic leukemia patients and the likelihood of relapse when taking dasatinib. 22 However, only 15 patients were studied, and all had Ն 2 mutations, which may signify high clonal diversity in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved either by the acquisition of mutations rendering the inhibitor ineffective or by activating a kinase distinct from the one being inhibited. [20][21][22][23] Thus, targeting STATs holds the promise of being useful against a wide spectrum of tumors, and for decreasing the emergence of resistance to kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%